The effect of the price of medical services and the personal traits of medical personnel on brand image mediated by the quality of health services - Bryan John Junior; Hery Winoto Tj; Fushen Fushen (Institute of Computer Science (IOCS), 2023)
The purpose of this study was to determine the effect of the price of medical services and the personal traits of medical staff on brand image which is mediated by the quality of health services. The population in this study were patients who had visited/treated the Pratama Medizen Clinic and were processed using Structural Equation Model (SEM) analysis with SEM PLS software. The research method used in this study is quantitative. Based on the results of the study, empirical facts were obtained in the form of: 1) The price of medical services has a positive effect on brand image; 2) Personality traits have a positive effect on brand image; 3) Service quality has a positive effect on brand image; 4) The price of medical services has a positive effect on the quality of health services provided; 5) Personality traits of medical personnel have a positive effect on service quality; 6) Service quality mediates the effect of medical service prices on brand image; 7) Quality of service mediates the influence of personality traits of medical personnel on brand image. Determining the price of medical services is adjusted to the economic conditions and capabilities of the community. The character and personality of the medical personnel is strived to be uniform so that consumers feel comfortable when receiving health services. The quality of service is further improved to create patient satisfaction so as to create a positive brand image of Pratama Medizen Clinic. The implication of this research is that it can use other variables that influence brand image to perfect the research results, it can also be carried out in different health clinics so that it will be a more comprehensive research, can be carried out on the same topic, so it is better to use different respondents and increase the number of samples and complete the theoretical basis of the research in more detail so that the resulting analysis results are more accurate.